Analysis on the Development Path and Potential of Electrification Level in the Field of Transportation in China. Issue 4 (May 2019) - Wang, Chengjie; Liu, Xiaocong
Abstract: In view of the current low level of electrification in global and Chinese transportation, this paper selects five key areas to improve the level of electrification, such as electric vehicle, urban rail transit, electrified railway, ship shore power and airport bridge equipment, carries out technical and economic analysis, and studies and evaluates the future development trend of the five technologies. Finally, according to the situation in 2020 and 2030 respectively, this paper carried out the calculation of electrification improvement potential. The research results provide a key path for improving the electrification level in the field of transportation, and analyze the feasibility and future potential of the path, providing a reference for the global and Chinese governments to improve the electrification level in the field of transportation.